Saddle-node equilibrium points on the stability boundary of nonlinear autonomous dynamical systems. Issue 1 (2nd January 2018) - Amaral, Fabíolo Moraes; Alberto, Luís Fernando C.; Gouveia, Josaphat R. R.
ABSTRACT: A complete characterization of the stability boundary of an asymptotically stable equilibrium point in the presence of type- k saddle-node non-hyperbolic equilibrium points, with k ≥ 0, on the stability boundary is developed in this paper. Under the transversality condition, it is shown that the stability boundary is composed of the stable manifolds of the hyperbolic equilibrium points on the stability boundary, the stable manifolds of type-0 saddle-node equilibrium points on the stability boundary and the stable centre and centre manifolds of the type- r saddle-node equilibrium points with r ≥ 1 on the stability boundary. This characterization is the first step to understanding the behaviour of stability regions and stability boundaries in the occurrence of saddle-node bifurcations on the stability boundary.